Knowledge, attitude and practice of pharmacovigilance among medical students - Kharadi, Darshan; Doshi, Chintan M. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Spontaneous reporting of adverse drug reaction (ADR) is main part of pharmacovigilance. This study was done to assess knowledge, attitude and practice (KAP) of pharmacovigilance among 2nd year medical students. Methods: This was a questionnaire based cross sectional study. The study participants were 2nd year MBBS students at pacific institute of medical sciences. Total number of questions given was 20. The data was analyzed by MS excel. Results: Total 100 students were given 20 questions. Among 20 questions, 10 were based on knowledge, 4 were based on attitude and 5 were based on practice. One question was asked to determine the reasons for underreporting. 95% students gave correct definition of pharmacovigilance. 96% students were having knowledge about existing National pharmacovigilance programme of India. 97% gave correct answer of side effect occurring during pregnancy as teratogenicity. 99 % said that reporting ADR is necessary. Conclusions: In our study most of the students gave correct answers of knowledge based questions. So knowledge of pharmacovigilance is gradually improving among medical students.